KD605 ナンキョク カンソクヨウ セツジョウシャ ノ ナンキョクテン リョコウ キロク - 細谷, 昌之; ホソヤ, マサユキ; HOSOYA, Masayuki (国立極地研究所, 1970)
P(論文) Three snow vehicles, type KD60, were successfully used by the traverse party of the 9th JARE (Japanese Antarctic Research Expedition) which made a round trip along 43°E in longitude from Syowa Station to the South Pole (direct distance : 5,180 km) during a period from September 1968 to February 1969 (141 days). This paper deals with one of the vehicles, KD605, which has an overall cab, 7.2 ton in weight, and is equipped with a super-charged diesel engine. It is also provided with a navigation system, several berths for the crew and cooking space, snow melter, and some racks built in for installing observation and radio equipments. In addition, to endure the severe environment of low temperature (-60℃) and high altitude of 4,000 meters, special care was taken in selecting the materials and in making the inhabitants comfortable. The vehicle covered 5,353 km within 110 days for driving and 31 days for camping, consuming 12,068 litres in total of diesel fuel. The snow surface was relatively hard from Syowa Station to 75°S. On the upward slope, drifting and blowing snow caused by katabatic wind was intense. In some areas the snow vehicle and sleds were stuck into soft snow accumulated by wind or due to the surface configuration. The highest area along the route was a plateau more than 3,500 meters between 75°S and 80°S. Soft snow covers this plateau where the wind was very weak and the air temperature was below -50℃. Snow vehicle tracks sank as deep as 30 cm into the snow and the fuel consumption rate rose as high as 3.5 l/km. Stopping longer than 5 minutes caused the runner of sled to stick to the snow surface, so that starting without help became impossible. Sticking was more pronounced with the decrease of air temperature. On the high plateau, more than 3,700 meteis in altitude, the exhausted gas became dark due to the shortage of air and the increasing resistance. As a result, apparent output lowering was accompanied by knocking sounds while the engine was driven at low to medium speed. In the terrain ...